Chronic myeloproliferative neoplasms with concomitant CALR mutation and BCR::ABL1 translocation: diagnostic and therapeutic implications of a rare hybrid disease - Zanelli, Magda; Fragliasso, Valentina; Loscocco, Giuseppe Gaetano; Sanguedolce, Francesca; Broggi, Giuseppe; Zizzo, Maurizio; Palicelli, Andrea; Ricci, Stefano; Ambrogi, Elisa; Martino, Giovanni; Aversa, Sara; Coppa, Francesca; et al. (Frontiers in Cell and Developmental Biology, 2024)
Myeloproliferative neoplasms (MPNs) are subdivided into Philadelphia (Ph) chromosome-positive chronic myeloid leukemia (CML) and Ph-negative MPNs. BCR::ABL1 translocation is essential for the development and diagnosis of CML; on the other hand, the majority of Ph-negative MPNs are characterized by generally mutually exclusive mutations of Janus kinase 2 (JAK2), calreticulin (CALR), or thrombopoietin receptor/myeloproliferative leukemia (MPL). CALR mutations have been described essentially in JAK2 and MPL wild-type essential thrombocythemia and primary myelofibrosis. Rarely coexisting CALR and MPL mutations have been found in Ph-negative MPNs. BCR::ABL1 translocation and JAK2 mutations were initially considered mutually exclusive genomic events, but a discrete number of cases with the combination of these genetic alterations have been reported. The presence of BCR::ABL1 translocation with a coexisting CALR mutation is even more uncommon. Herein, starting from a routinely diagnosed case of CALR-mutated primary myelofibrosis subsequently acquiring BCR::ABL1 translocation, we performed a comprehensive review of the literature, discussing the clinicopathologic and molecular features, as well as the outcome and treatment of cases with BCR::ABL1 and CALR co-occurrence.